Pengaruh Strategi Manajemen Harga Terhadap Tingkat Pendapatan Alfamart di Watampone - Ashari, Aisyah; Abdulahanaa; Rahma Hidayati Darwis (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
This study examines the impact of price management strategies on the revenue growth of Alfamart in Watampone. In the modern retail industry, pricing strategies are a crucial factor in attracting customers and enhancing competitiveness. The research employs a quantitative approach using simple linear regression to analyze the relationship between pricing strategies and revenue. Data were collected through questionnaires distributed to 36 respondents from 18 Alfamart stores in Watampone. The analysis results show that pricing strategies have a significant influence on revenue, with a coefficient of determination (R²) of 0.68, indicating that 68% of the variation in revenue is explained by pricing strategies. Furthermore, the t-test results reveal a significance value of 0.001, which is less than 0.05, indicating a strong and significant relationship. Therefore, implementing appropriate pricing strategies, such as discounts and loyalty programs, is proven to be effective in boosting company revenue. These findings contribute to retail management by providing insights into designing more optimal pricing policies to enhance competitiveness and profitability.